Distinct monocyte subset phenotypes in patients with different clinical forms of chronic Chagas disease and seronegative dilated cardiomyopathy - Pérez-Mazliah, Damián E (2018)
Fil: Pérez-Mazliah, Damián E. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Parasitología; Argentina.